2005
DOI: 10.1136/bmj.38583.728484.3a
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioural reactions to the bombings in London on 7 July 2005: cross sectional survey of a representative sample of Londoners

Abstract: Objectives To assess the impact of the bombings in London on 7 July on stress levels and travel intentions in London's population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
6
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(142 citation statements)
references
References 12 publications
9
120
6
7
Order By: Relevance
“…Although they were only a very small subgroup in our study, this finding is in line with other studies after terrorist attacks (Rubin et al, 2005; Schuster et al, 2001; Stein et al, 2004). Studies in Israel showed that populations associated with the offenders do not suffer less than the populations that are the explicit target of terrorists (Bleich et al, 2003; Cohen & Eid, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although they were only a very small subgroup in our study, this finding is in line with other studies after terrorist attacks (Rubin et al, 2005; Schuster et al, 2001; Stein et al, 2004). Studies in Israel showed that populations associated with the offenders do not suffer less than the populations that are the explicit target of terrorists (Bleich et al, 2003; Cohen & Eid, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…It is however remarkable that violence ‘in the name of religion’ affects religious people the most. An alternative explanation might be that these people felt more vulnerable because of their limited income or because of threat from the terrorist attacks and from being mistakenly affiliated with its origin (Rubin et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial stress level (SL). To compare our data with those from previous studies (Matt & Vazquez, 2006;Rubin et al, 2005;Schuster et al, 2001;Stein et al, 2004), SL was defined as a response of 4 or 5 to one or more than five PCL-C items.…”
Section: Post-traumatic Symptoms (Criteria B C and D Dsm-iv)mentioning
confidence: 99%
“…113 In sum: the process of vicarious retribution is clearly visible after the Al Qaeda attacks and has had real effects for the Muslim population of Western countries. …”
Section: Vicarious Retributionmentioning
confidence: 99%